Burden, duration and costs of hospital bed closures due to acute gastroenteritis in England per winter, 2010/11–2015/16. Issue 1 (September 2017) - Sandmann, F.G.; Jit, M.; Robotham, J.V.; Deeny, S.R.
Summary: Background: Bed closures due to acute gastroenteritis put hospitals under pressure each winter. In England, the National Health Service (NHS) has monitored the winter situation for all acute trusts since 2010/11. Aim: To estimate the burden, duration and costs of hospital bed closures due to acute gastroenteritis in winter. Methods: A retrospective analysis of routinely collected time-series data of bed closures due to diarrhoea and vomiting was conducted for the winters 2010/11 to 2015/16. Two key issues were addressed by imputing non-randomly missing values at provider level, and filtering observations to a range of dates recorded in all six winters. The lowest and highest values imputed were taken to represent the best- and worst-case scenarios. Bed-days were costed using NHS reference costs, and potential staff absence costs were based on previous studies. Findings: In the best-to-worst case, a median of 88, 000–113, 000 beds were closed due to gastroenteritis each winter. Of these, 19.6–20.4% were unoccupied. On average, 80% of providers were affected, and had closed beds for a median of 15–21 days each winter. Hospital costs of closed beds were £5.7–£7.5 million, which increased to £6.9–£10.0 million when including staff absence costs due to illness. Conclusions: The median number of hospital beds closed due to acute gastroenteritis per winter was equivalent to all general and acute hospital beds in England being unavailable for a median of 0.88–1.12 days. Costs for hospitals are high but vary with closures each winter.